The Effect of Self-Hypnosis on Reducing Blood Pressure in Elderly People with Hypertension in the Rawasari Community Health Center Work Area, Jambi City - Putra, Hadi Nazipatul; Kamariyah; Yuliana; Sari, Putri Irwanti; Martawinarti, RTS Netisa (Jurnal Pinang Masak, 2026)
Background: The prevalence of hypertension covers 100 million people aged 30–79 years in 184 countries, Hypertension is a major risk factor that causes diseases such as stroke, heart failure, stroke and nephrosis. Self hypnosis can control several organic functions such as bleeding, rapid heartbeat, blood pressure and so on. Aims: This study aims to determine the Effect of Self Hypnosis on Reducing Blood Pressure in the Elderly with Hypertension in the Rawasari Community Health Center Work Area, Jambi City. Methods: The population of this study was 1,408 people who visited the Rawasari Community Health Center who suffered from hypertension in 2024. The sampling method used was Purposive Sampling. The sample taken was 15 respondents. Results: The results of the study obtained Before Self Hypnosis, the average value of systolic blood pressure was 166.53 and diastolic 93.27 and after Self Hypnosis, the average value of systolic blood pressure was 151.13 and diastolic 83.07. The effect of Self Hypnosis on blood pressure in elderly with hypertension obtained the results of the Wilcoxon Signed-Rank Test, namely systolic p = 0.001 and diastolic p = 0.001 < 0.05. So it can be interpreted that there is a significant difference in blood pressure before and after treatment on both variables. Conclusion: It can be concluded that H1 is accepted so that this shows that the treatment given has a significant impact on changes in blood pressure.